School readiness of children with cerebral palsy - Gehrmann, F.; Coleman, A.; Weir, K.; Ware, R.; Boyd, Roslyn (2014)
Aim: To examine school readiness in preschool-age children with cerebral palsy (CP) on three of five domains compared with reported norms of children with typical development (CTD). Method: A representative population of 151 preschool-age children with CP (87 males, 64 females; 131 [87%] with spasticity, 17 [11%] dyskinesia, 3 [4%] hypotonia) were assessed at 48 or 60 months corrected age. Children were functioning in the following Gross Motor Function Classification System (GMFCS) levels: I, 74 (49%); II, 17 (11%); III, 14 (9%); IV, 26 (17%); V, 20 (13%). Children's motor performance, self-care, and social function were assessed using the Pediatric Evaluation of Disability Inventory (PEDI) and communication using the Communication and Symbolic Behaviour Scales Developmental Profile (CSBS-DP). Results were compared with a reference sample of CTD (PEDI CTD n=412; CSBS-DP CTD n=790). Linear regression was used to compare these data by functional severity. Results: Children with CP had significantly lower PEDI scores in all domains than CTD. Self-care scores ranged from 0.5 to more than 4SD below CTD, motor performance was 2 to >4SD below CTD, and social function between 0.5 and >4SD below CTD. Fifty-five per cent of children demonstrated significantly delayed communication skills. Non-ambulant children displayed significantly lower scores than ambulant children. Interpretation: Preschool-age children with CP perform significantly below their peers in three of five key readiness-to-learn skill areas including mobility, self-care, social function, and communication abilities. Broader emphasis needs to be placed on multimodal screening and intervention to prepare children with CP for school entry. © 2014 Mac Keith Press.